The Effect of Various Training Methods Exercises in Developing the Muscular Strengths of the Agonist Muscles for Swordsmanship Skills - Talib Hamadi, Firas; Hameed Abdullah, Mushtaq (International Journal of Psychosocial Rehabilitation, 2020)
According to the witnessed world's developments, especially in sport field, there are many methods in developing the capabilities of players, whether these capabilities are skill-specific to sports practice or physical and there are many methods and theories of training from which the coach can create an effective training curriculum that can improve performance and hence the research importance lies through the use of exercises with various training methods and getting benefit from it as a means to develop the level of Diyala Sports Club in a fencing game, while the research problem lies in the experience of The Researcher being one of the games’ specialists, he noticed that there is a weakness in the exercises of the muscular strengths of the dueling players due to lack of familiarity with the appropriate training methods to develop The level of the players, especially the character of the strengths of the muscles of the hands and feet. The researcher used the experimental approach for its suitability to the nature and problem of the research; he conducted the exploratory experiment and pre-tests and applied his exercises according to the main experience of the research and then the post-tests in the same conditions for the pre-tests. The researcher used the statistical bag Spss to extract the results and by which the researcher concluded that the training methods that used and included Plyometric training in developing the muscular strengths of the agonist muscles for swordsmanship skills for Diyala Sports Club players in a fencing game.